Efecto de las altas presiones hidrostáticas sobre la calidad y vida útil de duraznos mínimamente procesados : aspectos bioquímicos, fisicoquímicos, higiénico-sanitarios, nutricionales y sensoriales - Denoya, Gabriela Inés (2015)
Consumers demand fresh-cut fruits, free from additives and with fresh appearance. However, the alteration caused by the processing to the tissues limits their shelf life. The aim of this work was to study the effect of High Pressure Processing (HPP) on the preservation of minimally processed peaches. Cubes/cylinders of peaches were processed by combining a dipping pre-treatment in organic acids solution, with vacuum-packing and HPP at room temperature. HPP conditions were optimized, with the combination 600MPa-5min being able to cause the greater enzyme inactivation with a minimum alteration of the color and texture. Besides, it was studied the relevance of selecting varieties with low polyphenoloxidase activity as raw material, to control the enzymatic browning. Moreover, some biochemical processes (e.g. the expression and activity of enzymes) were still active in the pressurized peaches and, although HPP modified some characteristics of the living tissues, the pressurized products keep the appearance, texture and flavor of the fresh fruit. Finally, it was determined that the optimal storage temperature was 4°C, which allows a suitable preservation of the final product for 42 days without any microbial and sensorial deterioration. Interestingly, it was found that at 20°C the product can be maintained with suitable commercial quality.